2012
DOI: 10.1039/c1mt00124h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances into vanadyl, vanadate and decavanadate interactions with actin

Abstract: Although the number of papers about ''vanadium'' has doubled in the last decade, the studies about ''vanadium and actin'' are scarce. In the present review, the effects of vanadyl, vanadate and decavanadate on actin structure and function are compared. Decavanadate 51 V NMR signals, at À516 ppm, broadened and decreased in intensity upon actin titration, whereas no effects were observed for vanadate monomers, at À560 ppm. Decavanadate is the only species inducing actin cysteine oxidation and vanadyl formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Globally, the biological role of decavanadate may partly result by its capacity to interact with actin and to affect several biological processes where actin may be involved. It was concluded that[493]: (i) V10 and V IV O 2+ inhibit actin polymerization at M concentrations; (ii) only interaction of V 10 with actin induces cysteine oxidation and formation of V IV , these effects being prevented by ATP; (iii) decavanadate and V IV O 2+ induce actin conformational changes affecting the protein ATP binding site; (iv) actin has high affinity binding sites for V IV O 2+ .…”
mentioning
confidence: 98%
“…Globally, the biological role of decavanadate may partly result by its capacity to interact with actin and to affect several biological processes where actin may be involved. It was concluded that[493]: (i) V10 and V IV O 2+ inhibit actin polymerization at M concentrations; (ii) only interaction of V 10 with actin induces cysteine oxidation and formation of V IV , these effects being prevented by ATP; (iii) decavanadate and V IV O 2+ induce actin conformational changes affecting the protein ATP binding site; (iv) actin has high affinity binding sites for V IV O 2+ .…”
mentioning
confidence: 98%
“…26 Decavanadate was observed to induce protein cysteine oxidation and vanadyl formation in the presence of SR Ca 2+ -ATPase and actin, whereas no effects were observed on incubation with monomeric vanadate. 7,10,27 This reactivity of V 10 was attributed to the involvement of cysteines at the V 10 -binding site, as well as the participation of reduced vanadyl (V IV -containing) species in the enzymatic inhibition process. 10 It is known that actin, in common with other proteins such as transferrin and albumin, contains a high affinity binding site for vanadyl.…”
Section: Introductionmentioning
confidence: 99%
“…10 It is known that actin, in common with other proteins such as transferrin and albumin, contains a high affinity binding site for vanadyl. 7 Decavanadate interactions with certain proteins can thus lead to vanadyl protein binding, although the participation of vanadyl in the process is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on G-actin polymerization is important in maintaining the integrity of cytoskeleton and also in muscle contraction. The interaction of decavanadate with G-actin was described as follows: decavanadate oxidizes cysteine thiol group with concurrent formation of vanadyl ions at first, and then the vanadyl ions bind to actin, causes conformation change, and finally inhibition of G-actin polymerization (Aureliano 2011;Ramos et al 2006Ramos et al , 2012. Differing from V 10 , monovanadate does not interact with the cysteine thiol and acts merely as a phosphate analogue.…”
Section: Binding Properties Of Decavanadatementioning
confidence: 99%